The Use of Weblog-Based Islamic Religious Education Learning Media as Media and Learning Resources in Increasing Student Learning Interest - Khamdani, Umar (Journal of Research and Educational Research Evaluation, 2023)
This study aims to determine the effectiveness of the use of weblog-based Islamic education (PAI) learning media as a learning resource in increasing student interest in learning at MA Hidayatul Mubtadi'in Malang City. This study used a qualitative research design. Field research, researchers go directly to the field conducted in schools through observation, interviews, and documentation studies, to obtain clear and representative data. The results of this study indicate, teachers use blog-based Islamic Religious Education learning media at MA Hidayatul Mubtadi'in Malang City. The use of blogs in the learning process of Islamic Religious Education as media and learning resources in the learning process has an impact on students' interest in learning, students at MA Hidayatul Mubtadi'in Malang City have an interest in learning Islamic Religious Education. Based on the results of the study, it can be concluded that the use of blog-based Islamic Religious Education learning media at MA Hidayatul Mubtadi'in Malang City has a positive impact on students' interest in learning. The contribution of this research is to provide an alternative to innovative learning media in increasing students' interest in learning Islamic Religious Education subjects.